Upaya Masyarakat Dalam Meningkatkan Perekonomian Melalui Limbah Kelapa Sawit - Resdati; Hesti Asriwandari; T Romi Marnelly; Achmad Hidir; Yusmar Yusuf (Postgraduate, University of Mataram, 2024)
This research was implemented in Sukamaju Village, Sub regency of Singingi Hilir, Regency of Kuantan Singingi to know the potential of palm oil waste that is used by the society of Sukamaju Village as the manure and to describe the society effort of Sukamaju Village in using the potential of palm oil waste for increasing the economy level and decreasing the bad environment impact because of the palm oil waste. For obtaining the accurate data, the method of descriptive qualitative research is used by collecting the data, using the deep interview technique, direct observation and documentation. The analyze result shows that there is a quiet big waste potential in Sukamaju Village then processed to be the valuable manure. Moreover, this manure manufacture process is obtained from the palm oil waste from two big factories namely PT. Surya Agro Reksa and PT. Agrolestari. The process of waste production of palm oil includes the manufacture from the waste ponds, where the first pond of waste still has the high level of acidity so that it has not been able to be used yet. So the level of middle pond of waste water has been able to be channeled to the agriculture for make the plant fertile, and in the last level of solid waste is used as the natural manure of the land fertilizer. The analyze result shows that the waste of the palm oil can increase the fertility of land and plant, so it decreases the budget outcome of chemical manure. The socialization effort is needed to pressure massively for the information distributing connected the right waste processing.